Comportamento físico de materiais ferruginosos de solos da planície do rio Araguaia mediante diferentes tratamentos - Martins, Angélica Pires Batista (2017)
Ferruginous features occur frequently in soils of the Araguaia river plain, where profiles can be verified completely dominated by these characteristics. The objective of this study was to evaluate the physical variations in the plinthite and petroplinthite, considering: a) the compressive strength and stability of plinthic materials present in soils of the Araguaia river plain under natural drying and in a forced ventilation oven for different periods; b) the influence of different solutions and periods of immersion in the reversibility of hardening of plinthite and petroplinthite of the Araguaia river plain soils, both with the purpose of subsidizing the classification of these features. The study was carried out in five soil profiles in the Araguaia river flood plain, in Luiz Alves, district in the municipality of São Miguel do Araguaia, Goiás. A soil profile was also studied in Terezópolis de Goiás, Goiás, in the João Leite riverside flood plain. Soils samples were collected with PVC cylinders, directly in the plinthic horizons. From these samples were extract subsamples of plinthite and matrix of the soil. Homogenous samples of petroplinthite were also collected and separated into subsamples. Two experiments were carried out: in the first, plinthite, matrix of the soil and petroplinthite subsamples were submitted to two types of drying: in the natural environment and in a forced ventilation oven, and in the second, plinthite and petroplinthite subsamples were submitted to five hydration treatments: natural water, calcium carbonate solution, sodium hydroxide solution, sodium hydroxide + sodium hexametaphosphate solution and acid solution. The periods determined for the evaluations were 10, 20, 40, 80 and 160 days. The degrees of dispersion and stability and the compressive strength were evaluated. For the plinthite and petroplinthite of the same profile, there is a great variability of behavior as to the applied compression strength, which is associated with the iron contents that compose them. The immersion of plinthite and petroplinthite in solutions composed of chemical agents affects the dispersion, and the plinthite is more susceptible to the alkaline agents, with reduction of the compressive strength exercised.